Effect of light on the attachment of cyanophage AS-1 to Anacystis nidulans. - Cséke, C S (1979)
The effect of illumination on the extent and kinetics of the adsorption of cyanophage AS-1 to the blue-green alga (cyanobacterium) Anacystis nidulans was studied by using 32P-labeled phage. The initial rate of adsorption was not significantly affected by light. However, at Na+ levels used ordinarily to culture the alga ([Na+] = 11.7 mM), the total amount of phage adsorbed was doubled in the illuminated cultures, as compared with the dark-grown ones, over a wide range of multiplicities of infection (0.05 to 20). Upon a 10-fold increase in Na+ concentration in the medium ([Na+] = 0.11 M), the dark adsorption of the phage increased to the level of light adsorption found in low Na+ medium. The effects on phage adsorption of high Na+ concentration and light were not additive.